Assessing the Impact of Universal Healthcare Coverage on Maternal and Child Health Outcomes in Nigeria - Anuoluwaop Teleayo (Journal of Community Health Provision, 2023)
The purpose of this research was to determine how universal healthcare coverage in Nigeria would affect maternal and infant health. 500 households across four states in Nigeria provided information for this cross-sectional research. Data analysis using descriptive statistics revealed that the NHIS has helped increase access to and use of maternal and child healthcare services, leading to a decrease in maternal and child death rates. Inadequate funding, infrastructure, and health workforce were also cited as obstacles to implementing the NHIS in the study. Maximizing the NHIS's effect and achieving further gains in maternal and child health outcomes will require addressing these challenges and social determinants of health, such as poverty, education, and access to clean water and sanitation. These results have substantial implications for healthcare policymakers and providers in Nigeria and other low-income nations. Improving maternal and child health outcomes and decreasing household healthcare expenses are two major goals of universal healthcare coverage initiatives like the NHIS.